Spin effects in the process of associative production of the Higgs boson and W± boson - Manashova, M; Ahmadov, F. N. (Eurasian Journal of Physics and Functional Materials, 2026)
In this paper, we study the angular features of the signal and background processes of the associated production of the Higgs boson with W boson. Signal and background processes are generated using the CompHEP generator. Monte Carlo data is processed in ROOT software. In the course of studying the basic kinematic properties it was found that the shape of the distributions of the angular variables di ers for the signal and background processes. The presence of the spin e ect makes it possible to consider the di erence between the distributions of angular variables. The observed deviations can potentially reduce the background relative to the signal. Recommended Citation Manashova, M. A. and Ahmadov, F. N. (2020) "Spin effects in the process of associative production of the Higgs boson and W± boson," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 2, Article 3. DOI: https://doi.org/10.29317/ejpfm.2020040203